Zeitschrift für Religionswissenschaft (De Gruyter, 1993)
The journal provides a forum for exploring important methodological and theoretical issues and topics across the full breadth of the discipline, including related areas in the humanities, cultural studies, and the social sciences. It focuses on comparative studies about historical and contemporary European and non-European aspects of the history of religion and of contemporary religious culture.